2019
DOI: 10.18352/ijc.911
|View full text |Cite
|
Sign up to set email alerts
|

Tragedy of the inland lakes

Abstract: Increased pressure on communal fishing grounds is testing the traditional regulations among fishing communities who should preserve inland waters' productive capacity and ecological values. Inland lakes in Benin are a typical case in point. With the mounting number of fisherfolk and pollution from densely populated urban areas the threat of overfishing and water degradation looms large. This paper questions whether customary rules of fishing communities can cope with current and future challenges. A survey amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Moreover, the absence of the co-management of property rights with government does not favour the sustainable management of fishing ecosystems in southern Benin. These results are similar to those of Sonneveld et al [11] who demonstrated that fishing boundaries are not defined in southern Benin. Furthermore, the authors underline that there is no joint responsibility for resources governance in fishing areas of southern Benin as required by Ostrom's eight prerequisites for the sustainable and equitable development of common resources.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the absence of the co-management of property rights with government does not favour the sustainable management of fishing ecosystems in southern Benin. These results are similar to those of Sonneveld et al [11] who demonstrated that fishing boundaries are not defined in southern Benin. Furthermore, the authors underline that there is no joint responsibility for resources governance in fishing areas of southern Benin as required by Ostrom's eight prerequisites for the sustainable and equitable development of common resources.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this ban, the selection of locations for its implementation is governed by agreements between individuals, fishing communities, local authorities, but with very little public structure. This raises the low level of cooperation between fishers and public governance institutions [11].…”
Section: Evolution Of Ecological Protection Rules In Southern Beninmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, fishing lot abolishment created an open-access situation, where fishers harvested as much as possible, on the "first come, first served principle" without considering the collective negative effects on fish stocks, resulting in fishing down the food web or a recent indiscriminate fishing effect [7,49]. A similar situation has been described for many inland lakes around the world, leading to what has been termed "the tragedy of the inland lakes" [69]. Moreover, the declines are in part explained by the floodplain habitat alteration because substantial changes in land cover were observed recently during the ALA period, (e.g., decrease in scrubland, grassland, and flooded forest cover but increase in agricultural land), and flooded forest areas were shifted to woody savannah, grassland, and permanent wetland [31,[70][71][72].…”
Section: Discussionmentioning
confidence: 94%